Parents Using Medicine without a Doctor's Prescription: A Safe Habit? - Shelina Bhamani; Maliha Abbas; Sara Sheikh; Sahair Patel (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
This study, conducted at a tertiary care hospital in Karachi, Pakistan, delves into the alarming phenomenon of parental antibiotic misuse without medical consultation, posing a significant threat to antimicrobial resistance (AMR). A cross-sectional analysis involving 26 participants, predominantly educated mothers, reveals concerning trends. While 61.5% resort to over-the-counter/basic medicines for child ailments, 7.7% admit to administering antibiotics. Shockingly, 46.2% procure medications without prescriptions, and 15.4% advocate for antibiotics in young children. Significantly, 46.2% acknowledge the immunosuppressive impact of antibiotics, while 30.8% reserve antibiotic use for severe illnesses. These findings underscore the need for comprehensive guidelines regulating antibiotic prescription, particularly for pediatric cases. Collaboration between healthcare professionals and pharmacists is crucial for disseminating awareness about the hazards associated with self-medication. This study underscores the imperative to address this public health concern through targeted interventions and education initiatives.